2017
DOI: 10.3389/fncel.2017.00217
|View full text |Cite
|
Sign up to set email alerts
|

Differential SLC1A2 Promoter Methylation in Bipolar Disorder With or Without Addiction

Abstract: While downregulation of excitatory amino acid transporter 2 (EAAT2), the main transporter removing glutamate from the synapse, has been recognized in bipolar disorder (BD), the underlying mechanisms of downregulation have not been elucidated. BD is influenced by environmental factors, which may, via epigenetic modulation of gene expression, differentially affect illness presentation. This study thus focused on epigenetic DNA methylation regulation of SLC1A2, encoding for EAAT2, in BD with variable environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 62 publications
(80 reference statements)
0
12
1
2
Order By: Relevance
“…Future longitudinal research is warranted in order to establish the direction of causality in their relationship. Third, we did not consider the effect of some potential confounders, including heterogeneity in white blood cell composition 31 and cigarette smoking 32,33 , that may contribute to inter-individual variability in DNA methylation. In particular, since smoking can induce epigenetic modifications, the possible effect of smoking on DNA methylation should be considered in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Future longitudinal research is warranted in order to establish the direction of causality in their relationship. Third, we did not consider the effect of some potential confounders, including heterogeneity in white blood cell composition 31 and cigarette smoking 32,33 , that may contribute to inter-individual variability in DNA methylation. In particular, since smoking can induce epigenetic modifications, the possible effect of smoking on DNA methylation should be considered in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should include larger brain sample cohorts and balanced sample sizes between groups. Fourthly, some clinical factors known to modulate DNA methylation, such as last recorded mood state, nature of death, medications, and substance use history, could not be perfectly matched between subject groups ( Dell’Osso et al, 2014 ; Guidotti and Grayson, 2014 ; Huzayyin et al, 2014 ; Jia et al, 2017 ; Lohoff et al, 2017 ; McCullumsmith and Meador-Woodruff, 2011 ), thereby preventing statistical adjustment. Our findings might be partly attributed to these factors which were particularly complicated in BD and MDD cases.…”
Section: Discussionmentioning
confidence: 99%
“…We identified no studies investigating methylation differences between patients with a primary diagnosis of BED and normal-eater controls. However, one study reported that patients who showed concurrent bipolar disorders and binge-eating had hypomethylation of the SLC1A2 gene (involved in removing glutamate from the synaptic cleft) relative to patients with bipolar disorder who displayed no binge eating [68].…”
Section: Methylation Studies In Candidate Genesmentioning
confidence: 99%